The competitiveness of Trinidad and Tobago and manufacturing firms in an increasingly liberalised trading environment - Barclay, Lou Anne (2005)
Examines the competitive strategies implemented by successful Trinidad and Tobago exporters in the context of a liberalised trading environment. Opines that the future viability of Trinidad and Tobago's manufacturing sector rests on the purposeful efforts of both policy makers and firms.